Pengaruh Promosi Media Social dan Physical Evidence terhadap Keputusan Menginap : Survei pada Pengujung Hotel Crown di Tasikmalaya - Krisma Rama Nagara; Depy Muhamad Pauzy; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research is a quantitative research using survey method. The purpose of this research is to determine the effect of social media promotion and physical evidence to the decision to stay, either simultaneously or partially. The target population in this study are guests who stay at the Crown Hotel . Sampling technique using probability sampling with a simple random sampling approach . In this study, data collection was carried out using primary data and secondary data. The data collection technique used is by using a questionnaire. Based on the results of the study, classical assumption test, statistical analysis test, and hypothesis testing using SPSS 25, based on the results of the correlation analysis test, social media promotion has a very strong influence on the decision to stay, while physical evidence have a low influence on the decision to stay. The results of the F test show that social media promotion and physical evidence simultaneously have a significant effect on the decision to stay. Based on the T test, social media promotion and physical evidence partially have a significant effect on the decision to stay.